A second maternally expressed Drosophila gene encodes a putative RNA helicase of the "DEAD box" family. - de Valoir, T (1991)
Recently, a family of proteins containing the conserved motif Asp-Glu-Ala-Asp, the "DEAD box" proteins, has been identified. This family is typified by the eukaryotic translation initiation factor eIF4A, and its members are believed to share the functional property of ATP-dependent RNA unwinding. One of the previously identified members of this family (vasa) is the product of a maternally expressed gene from Drosophila melanogaster that is known to play a role in the formation of the embryonic body plan. We report here the isolation of a Drosophila gene that has an mRNA expression pattern somewhat similar to that of vasa and also encodes a DEAD box protein. We have termed this gene ME31B to reflect its maternal (ovarian germ-line) expression and its location within the 31B chromosome region. Comparisons with the other members of this family reveal that although ME31B is most like the protein Tif1/Tif2, which probably represents the Saccharomyces cerevisiae version of eIF4A, it is unlikely that ME31B represents the Drosophila eIF4A protein per se. A search for mutations in the ME31B gene has established that the P element which causes the female-sterile mutation flipper lies in the 3' flank of the ME31B gene.